2022 AFRICA AGRICULTURE TRADE MONITOR (AATM) - Bouet, Antoine; Odjo, Sunday; Zaki, Chahir (2022)
Antoine Bouet, Sunday Odjo, Chahir Zaki POLICY SEMINAR 2022 Africa Agriculture Trade Monitor (AATM) Leveraging Data to Improve Intra-Africa Food Trade Co-Organized by IFPRI and AKADEMIYA2063 SEP 27, 2022 - 9:30 TO 11:15AM EDT